Kemampuan Literasi Sains di Sekolah Dasar: Systematic Literature Review dan Bibliometric Analysis Periode Tahun 2016 - 2023 - Janah, Anisa Nur; Darmayanti, Mela; Saefudin, Asep (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to determine the development of research trends in science literacy skills of elementary school students in 2016-2023. The research methods used were bibliometric analysis and systematic literature review. Bibliometric analysis using VOSviewer. Researchers chose Google Scholar as a source of information. Documents related to science literacy were collected using the Publish or Perish application, then processed with the PRISMA method. The results of the review analysis of 109 science literacy articles in elementary schools in articles published in the period 2016-2023 showed that this research continues to grow. The journal that most frequently publishes science literacy articles is Basicedu Journal. The article with the most citations in 2017. The most published science literacy research subtopic is about learning media. Factors that influence the low level of science literacy in elementary school are inappropriate teaching materials. Meanwhile, factors that can improve science literacy in elementary schools are the active role of teachers, the learning environment, and adequate information technology. The impact of increasing science literacy is dominated by affective impacts in the form of scientific attitudes and responsibility, psychomotor impacts in the form of science process skills and critical thinking.